The costs and benefits of different initial teacher training routes - Rebecca Allen; Chris Belfield; Ellen Greaves; Caroline Sharp; Matt Walker (Institute for Fiscal Studies (IFS), 2014)
This report provides the first evidence of the relative cost-effectiveness of different routes into teaching in England, describing and empirically estimating the costs and benefits of different routes into teaching while accounting, as far as possible, for the selection of teachers with different characteristics into each route. Our specific research questions are grouped into three strands: recruitment, training and retention. This report summarises our findings for the first two strands: the costs and benefits for central government and schools related to recruitment and training, which can be thought of as short-term costs and benefits, answering the following questions:Recruitment - What are the characteristics of potential teachers who choose this route? What are the characteristics of schools that choose to take trainee teachers via this route? Training - What are the total costs of university-based components of training? What indirect costs are imposed on schools - for example, through supervision and mentoring? What are the benefits to schools - for example, through trainees' contribution to teaching and recruitment? What are the short-term differences in the effectiveness of departments receiving trainee teachers (in terms of pupils' academic attainment)?
Keywords: 330